The Influence Of Peer Group Education On Young Female Students' Knowledge Of Juvenile Delinquency Prevention At SMK Kartika IV-1 Malang City - Fransisca Erlita Dewi; Suprapti Suprapti; Reni Wahyu Triningsih; Ika Yudianti (Jurnal Maternitas Kebidanan, 2026)
Adolescence is a significant phase of individual development characterized by increased social and emotional drives, thus encouraging risky behavior (juvenile delinquency), including free sex, illegal abortion, and substance abuse. Therefore, health education is needed as an effort to prevent juvenile delinquency. One of the health education that can be applied is peer group education. Peer group education is an educational method that involves peers as facilitators to increase knowledge and shape positive behavior. This study aims to determine the effect of peer group education on increasing knowledge of adolescent girls about preventing juvenile delinquency at SMK Kartika IV-1 Malang City. This study used a quasi-experimental design with a pretest-posttest approach without a control group. The sample in this study were all 30 female students of grade X of the Beauty Department of SMK Kartika IV-1 Malang City. The instrument used was a multiple-choice questionnaire to measure the level of knowledge about preventing juvenile delinquency before and after the peer group education method was implemented. The data were analyzed using the Wilcoxon test and obtained a p-value of 0.000, so it can be concluded that the p-value is smaller than α, namely (0.000 <α), so it can be concluded that there is a significant effect of peer group education on increasing the knowledge of adolescent girls regarding the prevention of juvenile delinquency. Thus, this method can be recommended as an effective preventive education strategy among school adolescents.